(untitled) (Research, Society and Development, 2021)
In this study we evaluated the potential of Mauritia flexuosa leaves in the egg hatching and larval development inhibition and for reduction of egg count of this nematode in sheep feces. The leaves of this palm were collected and dehydrated for the production of aqueous and ethanolic extracts with and without tannins. Gas chromatography analysis indicated the presence of fifteen and ten major compounds in the aqueous and ethanolic extracts, respectively, and both showed catechin peaks. The total of condensed tannins for leaves of Mauritia flexuosa was 33.23% ± 2. Aqueous and ethanolic extracts showed 100% anthelmintic activity to inhibit hatchability at 75 mg/ml. The inhibitory concentrations LC90 for aqueous and ethanolic extracts were, respectively, 21.8 and 8.5 mg/ml. The dehydrated leaves powder of M. flexuosa at ≥ 152.08 mg / g of coproculture presented efficiencies greater than 80% for inhibition of larval development. The in vivo administration of aqueous extract at 62.1 mg/kg PC promoted anti-helminthic efficacy of 54.57% and, after 14 days, no clinical signs of toxicity and clinical changes were observed in the treated lambs, indicating potential of this extract for the control alternative of haemonchosis.